Severe thrombophilia in a factor V‐deficient patient homozygous for the Ala2086Asp mutation (FV Besançon). (8th April 2021) - Castoldi, Elisabetta; Hézard, Nathalie; Mourey, Guillaume; Wichapong, Kanin; Poggi, Marjorie; Ibrahim‐Kosta, Manal; Thomassen, M. Christella L. G. D.; Fournel, Alexandra; Hayward, Catherine P. M.; Alessi, Marie‐Christine; Hackeng, Tilman M.; Rosing, Jan; et al.
Abstract: Background: Coagulation factor V (FV), present in plasma and platelets, has both pro‐ and anticoagulant functions. Objective: We investigated an FV‐deficient patient (FV:C 3%, FV:Ag 4%) paradoxically presenting with recurrent venous thrombosis (11 events) instead of bleeding. Methods/Results: Thrombophilia screening revealed only heterozygosity for the F2 20210G>A mutation. Although thrombin generation in the patient's platelet‐poor plasma was suggestive of a hypocoagulable state, thrombin generation in the patient's platelet‐rich plasma (PRP) was higher than in control PRP and extremely resistant to activated protein C (APC). This was partially attributable to the complete abolition of the APC‐cofactor activity of FV and a marked reduction of plasma tissue factor pathway inhibitor antigen and activity. The patient was homozygous for a novel missense mutation (Ala2086Asp, FVBesançon ) that favors a "closed conformation" of the C2 domain, predicting impaired binding of FV(a) to phospholipids. Recombinant FVBesançon was hardly secreted, indicating that this mutation is responsible for the patient's FV deficiency. Model system experiments performed using highly diluted plasma as a source of FV showed that, compared with normal FVa, FVaBesançon has slightly (≤1.5‐fold) unfavorable kinetic parameters (Km, Vmax ) of prothrombin activation, but also a lower rate of APC‐catalyzed inactivation in the presence of protein S. Conclusions: FVBesançon induces a hypercoagulable state via quantitative (markedly decreased FV level) and qualitative (phospholipid‐binding defect) effects that affect anticoagulant pathways (anticoagulant activities of FV, FVa inactivation, tissue factor pathway inhibitor α level) more strongly than the prothrombinase activity of FVa. A possible specific role of platelet FV cannot be excluded.